SPECTRUM OF OPPORTUNISTIC FUNGAL INFECTIONS IN HIV/AIDS PATIENTS IN TERTIARY CARE HOSPITAL, JHARKHAND, EAST INDIA. - Sharma, Ashok Kumar; Boipai, Manju; Seema, Kumari; Kumar, Abhay; Kumar, Manoj (Student's Journal of Health Research Africa, 2023)
Background: HIV infection continues to be a major health problem with more than millions of AIDS-related death annually. As CD4+ cell count decreases in HIV/AIDS patients, the risk of opportunistic fungal infections increases resulting in high morbidity and Mortality. The spectrum of opportunistic fungal infections varies from one region to another. The purpose of the study was to investigate the occurrence of opportunistic fungal infection among HIV/AIDS-positive patients in Jharkhand. Method: This descriptive study was carried out at a tertiary care center in Jharkhand, over a period of two years. Total 118 HIV-positive patients with CD4+ count ≤200 cells/mm3 and suspected of having fungal infections were included. Samples were collected after taking an informed written consent from the patient. Isolation and identification of organisms were done as per standard Microbiological procedure. Result: Opportunistic fungal infection was identified in 47.45 % of patients. The most common fungi isolated were Candida species, Cryptococcus neoformans, Aspergillus species and Dermatophytes respectively being 27.96 % (n= 33), 12.71% (n= 15), 3.38 % (n= 4) and 3.38 % (n= 4). The commonest fungal agent is Candida species, comprising 58.92 %, followed by Cryptococcus neoformans 28.78 % of total fungal isolates. Conclusion: The common fungus isolated were Candida species, Cryptococcus neoformans, Aspergillus species, and Dermatophytes in HIV-positive patients in Jharkhand. This study would help to sensitize clinicians to make the correct diagnosis and plan appropriate strategies for the investigation and treatment of common opportunistic fungal infections at center.